2016
DOI: 10.18632/oncotarget.10135
|View full text |Cite
|
Sign up to set email alerts
|

Critical function of the necroptosis adaptor RIPK3 in protecting from intestinal tumorigenesis

Abstract: Necroptosis is a programmed form of non-apoptotic cell death that requires the kinase activity of the receptor interacting protein kinase 3 (RIPK3). Although in vitro data suggests that cancer cells lacking expression of RIPK3 are invasive, the physiological role of RIPK3 in a disease-relevant setting remains unknown. Here we provide evidence that RIPK3 has a critical role in suppressing colorectal cancer (CRC). RIPK3-deficient mice were highly susceptible to colitis-associated CRC and exhibited greater produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 67 publications
1
77
0
Order By: Relevance
“…Like in AML patients, in primary breast cancer samples RIPK3 loss correlated with methylation of the genomic region near RIPK3 gene's transcription start site, suggesting that a methylation‐mediated mechanism regulates RIPK3 expression during breast cancer development 19 (Table 1). Several reports found that RIPK3 is downregulated in human colon and colorectal cancers compared with adjacent normal tissues 22 , 28 , 29 . Accordingly, loss of Ripk3 increased colon tumourigenesis induced by carcinogens in mice.…”
Section: Necroptosis Tumourigenesis and Cancer Progressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Like in AML patients, in primary breast cancer samples RIPK3 loss correlated with methylation of the genomic region near RIPK3 gene's transcription start site, suggesting that a methylation‐mediated mechanism regulates RIPK3 expression during breast cancer development 19 (Table 1). Several reports found that RIPK3 is downregulated in human colon and colorectal cancers compared with adjacent normal tissues 22 , 28 , 29 . Accordingly, loss of Ripk3 increased colon tumourigenesis induced by carcinogens in mice.…”
Section: Necroptosis Tumourigenesis and Cancer Progressionmentioning
confidence: 98%
“…Accordingly, loss of Ripk3 increased colon tumourigenesis induced by carcinogens in mice. The acceleration of tumourigenesis in Ripk3 ‐deficient mice was more likely due to an excessive inflammation 28 . Therefore, the role of RIPK3 in dampening inflammation during colorectal tumourigenesis contrasted with its role in others inflammatory scenarios, where loss of Ripk3 has been described to limit inflammation 30 .…”
Section: Necroptosis Tumourigenesis and Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other cytokines ( Tnf-α , IL-1β , Interferon-γ ), inflammatory enzymes ( Cox-2 , Nos2 ), nuclear factor (NF)-κB, and signal transducer and activator of transcription 3 (Stat3) are also involved in inflammation-associated colorectal carcinogenesis [72]. Uncontrolled activation of Nf-κB, Stat3, and Wnt-β-catenin signaling pathways enhances the aberrant proliferation of crypal cells in the sustained inflammatory microenvironment and promotes CRC development [75]. Although we did not assay Stat3 and Nf-κB in the present study, the mRNA expression of Tnf-α , Il-1β , Il-6 , Cox-2 , and Nos2 was assayed in the colorectum of Apoe -deficient, Ldlr -deficient, and their respective WT mice treated with AOM and DSS.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotic regulators also seem to affect cancer prognosis. For example, low RIP3 levels are correlated with poor outcomes in colorectal and breast cancer patients [30][31][32]. RIP3 expression in the hematopoietic system may limit cancer invasion and metastasis.…”
Section: The Implications Of Programmed Necrosis For Cancer Therapymentioning
confidence: 99%